Problems of culture of written expression in primary school - Zlatić Marina V.; Đorđević Jelena Đ. (Sinteze, 2014)
This paper investigates the issue of the culture of written expression in primary school students. Starting from the fact that teaching practices increasingly points to the fact that knowledge of rules of writing in primary school students presents the weakest link in teaching Serbian language, we sought to describe the problem, point to the possible causes, propose measures and illustrate all this on concrete examples of students' essays. Our microinvestigation showed that primary school students display considerably poorer mastery of rules of writing than previously thought, to the extent that it presents a serious obstacle in language teaching as well as in other areas of educational process.